ANALISIS PENGARUH VARIASI MATERIAL CORE TERHADAP KUALITAS NIPPLE - Moh Rofi Julian; Yopi Handoyo (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2020)
This study aims to determine the effect of variations in core material made of iron and resin sand on the Nepel Brass smelter on hardness, surface results of castings, shrinkage, density apparent, time, and cost. To find out which core material is more efficient for use in large quantities. The product material used is Brass in the form of Hose Nipple with a size of 1/5 x 5/8 inch. The average specimen weight in this study was 8.33 gr. From the research conducted, the differences were found, namely the hardness of the smelting process with the core material of iron castings and resin sand is 37.14 BH 5 / 250-25 and 30.94 BH 5/250-25. Material defects found are in iron castings specimens, namely rough surface defects, pinhole, scrabs, gas holes and air voids with 19 points of defect points and an area of ​​78 mm or 10.57% of the inside area of ​​the specimen. Likewise with resin sand-coated specimens experiencing defects of Coarse Surface, Needle Hole, Scrabs, Gas Hole, Air Cavity and sand inclusion / erosion hardness, with large numbers almost covering all parts of the specimen or 95.1%. For shrinkage, cast specimens with iron castings are smaller at 0.35% and resin-coated specimens of 0.40%. For porosity defects, iron castings in the specimens were 8.33 and 8.40 in the core of the resin sand castings. The higher the true density, the more dense the material is. The production time is 555 seconds (9 minutes 15 seconds) from the smelting process of specimens with the core of resin sand castings which is for 829 seconds (13 minutes 49 seconds). Whereas for the process of releasing specimens from molds, products with resin sand castings are faster at 14 seconds, while for specimens with iron castings core is 28 seconds. The cost required to make specimens with iron cast core is Rp. 4,718,500, the cost is cheaper than the manufacture of specimens with core resin sand castings that require capital of Rp. 4,999,000.